2022
DOI: 10.3390/pharmaceutics14061183
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Strain-Probiotic-Loaded Nanoparticles Reduced Colon Inflammation and Orchestrated the Expressions of Tight Junction, NLRP3 Inflammasome and Caspase-1 Genes in DSS-Induced Colitis Model

Abstract: Gut modulation by multi-strain probiotics (MSPs) is considered an effective strategy for treating inflammatory bowel disease (IBD). The combination of nanomaterial-based MSPs can improve their viability and resistance and can allow their targeted release in the gastrointestinal tract to be achieved. Thus, our aim is to investigate the prospective role of MSP integration into nanomaterials (MSPNPs) and the underlying molecular mechanisms supporting their application as an alternative therapy for IBD using a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…This elevation in fecal calprotectin signifies the migration of neutrophils into the intestinal mucosa as a consequence of intestinal injury [ 67 ]. An elevation in FC was detected in colitic non-treated rats, unlike the group treated with multi-strain-loaded nanoparticles [ 25 ]. Remarkably, the current study showed that the positive impacts of QT-NPs on FC reduction were more prominent when their levels were increased after the induction of colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This elevation in fecal calprotectin signifies the migration of neutrophils into the intestinal mucosa as a consequence of intestinal injury [ 67 ]. An elevation in FC was detected in colitic non-treated rats, unlike the group treated with multi-strain-loaded nanoparticles [ 25 ]. Remarkably, the current study showed that the positive impacts of QT-NPs on FC reduction were more prominent when their levels were increased after the induction of colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the fact that quercetin can be absorbed in the stomach and small intestine and rapidly metabolize or suffer strong degradation may hinder its access to the colon at desired concentrations to display local antioxidant and anti-inflammatory effects, thus restricting its potential use for IBD management [ 23 ]. Hence, the engineering of innovative dietary formulations targeting nanoparticles (NPs) offers functional food ingredients with various novel features that enhance their bioavailability, quality and safety together with increasing their stability and protecting them from intestinal degradation [ 24 , 25 , 26 , 27 ]. The fate of nanoparticle-based functional ingredients in the gastrointestinal tract greatly varies from that of ingredients that have larger particles owing to their higher surface area with greater motion proficiency, enabling them to easily penetrate the biological barriers, including intestinal epithelial cells [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that probiotic supplementation with either Lactobacillus paracasei, B. lactis, Lactobacillus rhamnosus, L. acidophilus , or with Lactobacillus rhamnosus , Bifidobacterium longum can accelerate trauma healing after surgeries, with better results when simultaneously using multiple strains [ 76 , 77 , 78 ]. The re-epithelialization in DSS-induced mice was also faster after treatment with Bifidobacterium bifidum , L. acidophilus and Bacillus amyloliquefaciens [ 79 ] In a study by Tsai et al, the co-administration of heat-killed L. plantarum and Lactobacillus paracasei promoted healing in mice [ 80 ], while Kazemi et al showed that the extracts of L. plantarum and Lactobacillus casei promoted the proliferation of mesenchymal stem cells [ 81 ]. Furthermore, a four-strain supplement containing L. acidophilus, L. plantarum, Lactobacillus rhamnosus and Enterococcus faecium benefited epithelial tight junction integrity and promoted wound healing [ 82 ], and another one containing L. acidophilus, L. plantarum, B. lactis and Bifidobacterium breve can strengthen the epithelial barrier of the gut [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, higher expression levels of ZO-1 , CLDN-1 , occludin, MUC-2, and JAM-2 in the intestine of rabbits described that MSP, especially at higher doses, enhanced TJPs. In accordance, probiotics could enhance gut barrier function by increasing the expression of TJP genes [ 106 , 107 , 108 ]. Moreover, some Lactobacillus species, such as L. plantarum, abated barrier disruption via upregulation of TJPs [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%